2021
DOI: 10.1177/0271678x211026771
|View full text |Cite
|
Sign up to set email alerts
|

Review of treatment and therapeutic targets in brain arteriovenous malformation

Abstract: Brain arteriovenous malformations (bAVM) are an important cause of intracranial hemorrhage (ICH), especially in younger patients. The pathogenesis of bAVM are largely unknown. Current understanding of bAVM etiology is based on studying genetic syndromes, animal models, and surgically resected specimens from patients. The identification of activating somatic mutations in the Kirsten rat sarcoma viral oncogene homologue (KRAS) gene and other mitogen-activated protein kinase ( MAPK) pathway genes has opened up ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 145 publications
(191 reference statements)
0
11
0
Order By: Relevance
“…In previous monoculture and animal models, MEKi has been investigated as a possible treatment strategy 5,7,22,48,49 . In monocultures, MEKi re-established VE-cadherin to cell junctions and restored normal actin localization and cell shape by suppressing ERK phosphorylation 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous monoculture and animal models, MEKi has been investigated as a possible treatment strategy 5,7,22,48,49 . In monocultures, MEKi re-established VE-cadherin to cell junctions and restored normal actin localization and cell shape by suppressing ERK phosphorylation 5 .…”
Section: Discussionmentioning
confidence: 99%
“…A key future step in the improvement of the clinical management of brain AVMs would be the development of novel anti-angiogenic therapies 336 , 337 , for instance targeting the pathways downstream of KRAS mutations with MEK inhibitors (which are already approved for the treatment of brain tumours 338 , 339 ) or other targets emanating from single-cell studies 75 , 163 , 265 . For explorations of the future clinical and pharmacological treatment of brain AVMs, we refer readers to recent reviews on this topic 336 , 337 .…”
Section: Angiogenesis In Brain Avmsmentioning
confidence: 99%
“…Recent research has contributed to delineating the processes involved in bAVM development, progression, and bleeding (95). The RAS/MAPK/ERK signaling pathway is a common route with peripheral AVMs, and the recent finding of somatic gene mutations in bAVMs has added to the growing list of significant signaling pathways involved in bAVM and isolated potential targets to stabilize vascular tissue thereby decreasing the risk of spontaneous ICH (96). In mice specific model, treated with bevacizumab or trastuzumab, Walker et al reported reduction in dysplastic vessels (97).…”
Section: Accepted Manuscriptmentioning
confidence: 99%